RELATIONSHIP BETWEEN PARTICULATE MATTER (PM10), METEOROLOGICAL PARAMETERS, AND THE CONCENTRATION OF FUNGAL SPORES IN THE ATMOSPHERE OF SAN MARTÍN SQUARE IN LIMA - Ramos, Roberto (2023)
The relationship between the concentration of particulate matter with aerodynamic diameter ≤ 10 µm (PM10), meteorological variables (air temperature, relative humidity, UV index, and wind speed), and the concentration of total fungal spores in the outdoor air of Plaza San Martin in Lima was studied. The sampling of fungal spores was performed using a single-stage Andersen-type volumetric impact equipment; PM10 values were provided by the Mobile Station of La Colmena (PROTRANSPORTE – Municipality of Lima). The results show that the concentrations of PM10 were highest in the months of March and April, which coincide with the highest concentrations of total spores, and continuously decreased to a minimum in the months of June and July. PM10 concentration showed a strong positive correlation with total spore concentration. Regarding the influence of meteorological variables on the concentration of PM10, a non-significant positive correlation was found with wind speed (r = 0.727). Air temperature and UV index presented a positive correlation with a significance level p < 0.001. Concerning relative humidity (RH), PM10 presented a negative correlation with a significance level p < 0.05. Further studies are required to evaluate the concentrations of PM10 in relation to the concentrations of fungal spores in the atmosphere of San Martin Square.